Perceptions of 2022 PBA UIN Datokarama Palu Students Regarding the Use of Duolingo in Improving Arabic Vocabulary Mastery - Khatiar Rahmat; Nursyam; Muh. Jabir; Ubay; Zaitun (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2025)
This study aims to describe the perceptions of students of the Arabic Language Education Department at UIN Datokarama Palu, Class of 2022, regarding the use of the Duolingo application in improving their Arabic vocabulary mastery. The research is based on the need for engaging and flexible learning media that can support continuous vocabulary acquisition, considering that conventional learning methods are often perceived as lacking variety and authentic contextual exposure to the Arabic language. This study employs a descriptive qualitative approach involving seven purposively selected students based on their active use of Duolingo. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that most students hold positive perceptions of Duolingo, particularly due to its interactive features such as reading, listening, writing, and speaking exercises, which help enrich vocabulary gradually. Gamification elements, including points, levels, and daily streaks, also contribute to increased motivation and consistency in independent learning. However, several challenges are also identified, including limited vocabulary relevant to academic needs, dependence on a stable internet connection, and a tendency among some learners to pursue streaks without fully understanding the material. Overall, Duolingo is viewed as a sufficiently effective supplementary tool for enhancing Arabic vocabulary mastery, although its use becomes more optimal when combined with contextual materials and supported by lecturer guidance in formal learning environments.